Latin American Television: A Global View - Sinclair, John (Oxford University Press, 1998)
Latin American Television makes English speakers aware of the dimensions, operation, and significance of the globalization of television in the Spanish-speaking world. Second only in scale to the market for English-language programming, the Spanish-language market embraces not just most nations of South and Central America but also Spain, and even the United States–the sixth largest Spanish-speaking country in the world. This intercontinental space is connected physically by satellite communication, and culturally by a common language and heritage which binds it as both a `geolinguistic region' and an `imagined community' which certain media corporations, Latin American and North American, seek to exploit. A similar phenomenon with regard to Brazil and the Portuguese-speaking world is ... Source: Publisher
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Océanie (lieu de production du savoir); Australie (lieu de production du savoir); _Nettoyé